Social identity perspective intergroup relations, self conception, and small groups - Hogg, Michael A.; Abrams, Dominic; Otten, Sabine; Hinkle, Steve (Sage Publication, 2004)
The historical development, metatheoretical background, and current state of the social identity perspective in social psychology are described. Although originally an analysis mainly of intergroup relations between large-scale social categories, and more recently an analysis with a strong social cognitive emphasis, this article shows that the social identity perspective is intended to be a general analysis of group membership and group processes. It focuses on the generative relationship between collective self-conception and group phenomena. To demonstrate the relevance of the social identity perspective to small groups, the article describes social identity research in a number of areas: differentiation within groups; leadership; deviance; group decision making; organizations; computer mediated communication; mobilization, collective action, and social loafing; and group culture. These are the areas in which most work has been done and which are therefore best placed for further developments in the near future.